Ядерно-ядрышковая изменчивость семенного потомства сосны меловой урожаев разных лет в заповеднике «Меловая флора» - Коршиков, И.И.; Мильчевская, Я.Г.; Ткачева, Ю.А.; Лаптева, Е.В. (Фактори експериментальної еволюції організмів, 2014)
Aims. Analysis of nuclear organizer activity in seed progeny of one and the same plant group in different years within a natural population of Pinus sylvestris L. var. cretacea Kalenicz. ex Kom. Methods. Nucleoli staining with AgNO₃ in interphase cells of seedlings. Results. Differences in cell areas were 1.5 times, in mean nuclear area per cell were 1.9 times in seed progeny of same age plants from the locality of “Melovaya flora” reserve natural population. Conclusion. Certain instability of quantitative and qualitative characteristics of nucleoli and nucleus-nucleolus ratio is observed in seed yield of P. sylvestris var. cretacea, sampled in two successive years.

Key words: nucleolus, seedlings.